2014
DOI: 10.1589/jpts.26.1791
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Peak Expiratory Flow and Abdominal Muscle Thickness

Abstract: [Purpose] The purpose of this study was to determine whether forced expiration is correlated with abdominal muscle thickness. [Subjects] Twenty-three healthy male volunteers participated in this study. [Methods] The peak expiratory flow (PEF) was obtained using a peak flow meter with subjects in the sitting position. The thicknesses of the right rectus abdominis, external oblique, internal oblique, and transverse abdominis muscles were measured using B-mode ultrasonography at the end of a relaxed expiration in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 34 publications
0
22
1
1
Order By: Relevance
“…IMT positively enhances respiratory muscle strength, which reflects the relative load for breathing, coughing, and huffing (14,15). Moreover, Sutton et al showed that improved forced expiration maneuvers could be more effective than coughing for improving clearance of bronchoalveolar hyper-secretions (16).…”
Section: Discussionmentioning
confidence: 99%
“…IMT positively enhances respiratory muscle strength, which reflects the relative load for breathing, coughing, and huffing (14,15). Moreover, Sutton et al showed that improved forced expiration maneuvers could be more effective than coughing for improving clearance of bronchoalveolar hyper-secretions (16).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that there was a positive association between diaphragmatic thickness and maximal inspiratory pressure 11 , 12 . A recent study found that the thickness of the external oblique muscle produced a higher correlation with peak expiratory flow among the abdominal muscles 13 . However, little is known about the association between each abdominal muscle thickness and maximal expiratory pressure.…”
mentioning
confidence: 99%
“…The remodelling phase is the last stage of healing, where a reorganisation of collagen takes place, leading to a greater tensile strength. 24 Sanatim et al 28 showed that a better healing of injured tissue was found in the treated groups, with emphasis on the elderly group. Our work confirms the findings of Sanatim et al 28 with an increased amount of collagen in the lesioned area of light-treated groups compared to untreated groups, with the LED-treated group more evident.…”
Section: -24mentioning
confidence: 99%
“…24 Sanatim et al 28 showed that a better healing of injured tissue was found in the treated groups, with emphasis on the elderly group. Our work confirms the findings of Sanatim et al 28 with an increased amount of collagen in the lesioned area of light-treated groups compared to untreated groups, with the LED-treated group more evident. Despite the differences in the power of both light sources used in the study, the energy was kept the same.…”
Section: -24mentioning
confidence: 99%